A theoretical study of low-velocity impact of metal foam-filled circular tubes. (March 2020) - Zhang, Jianxun; Ye, Yang; Yuan, Hui; Qin, Qinghua; Wang, T.J.
Abstract: In this paper, the low-velocity impact of metal foam-filled circular tubes are investigated. Based on the quasi-static method, an analytical model is developed to predict the plastic behaviors of the fully clamped metal foam-filled circular tube under the low-velocity impact. Effects of local denting and filled foam strength on the overall bending of the foam-filled tube are considered. Finite element analysis are conducted to study the dynamic response of clamped metal foam-filled circular tube. Good agreement is achieved between the analytical and numerical results. The effect of the filled foam on the dynamic response of the foam-filled tube is discussed. It is demonstrated that the present analytical model is valid to predict the low-velocity of foam-filled circular tubes. Highlights: Low-velocity impact of metal foam-filled circular tubes struck transversely by a heavy mass is investigated. An analytical model is developed to predict the plastic behaviors of metal foam-filled circular tube. The analytical model can capture the numerical results reasonably.